(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fintech means financial technology now these days various types of technologies are provided for banking sector. India has adopted information technology and has given the preference to internet banking. Fintech sector is playing a important role in reducing operation cost, management information system, point of scale technologies, ATM(automated teller machine), smart cards, mobile payment app (paytm, mobiwik, zaggle, pinelabs etc. Fintech plays important role towards banking sector progress and is anticipated to get bigger in coming times. As per research government should take proper action to up skill people towards the adequacy of digital money product. Formal assistance, pedagogy and guidance of the fintech services will bring down the number of traditional method of legal tender transaction in the economy. In this research paper the challenges opportunities and threats of banking sector have been discussed.